Towards an application framework for context-aware m-health applications. (9th February 2007) - Broens, Tom; Van Halteren, Aart; Van Sinderen, Marten; Wac, Katarzyna
Several social-economical developments, like the ageing society, stimulate the use of ICT applications for mobile healthcare (e.g., tele-monitoring). To support novel m-health applications, the consequences of developing these applications should be considered in the scope of a comprehensive architecture. Additionally, contextual information plays an important role for personalised healthcare and should be considered in such architectures. This paper describes ongoing research that focuses on developing an application framework for supporting the development of context-aware m-health applications. It gives initial requirements for such a framework and it gives a first attempt for a functional decomposition. The use of the framework is illustrated by means of an epilepsy tele-monitoring scenario.